THE INFLUENCE OF SPIRITUAL AND INTELLECTUAL INTELLIGENCE ON PERSONAL FINANCIAL MANAGEMENT WITH PEER GROUP MODERATION: (Case Study of Generation Z in Kefamenanu City) - Maximus Leonardo Taolin; Sarlince Sandy Mauk; Melania Derang (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This study aims to determine the influence of Spiritual Intelligence (SP) and Intellectual Intelligence (IP) on Personal Financial Management (PKP) with Peer Group Moderation (PG), a case study of Generation Z in Kefamenanu City. The population in this study was Generation Z in Kefamenanu City. The sample size was 160 respondents, calculated using the Ferdinand formula. The data analysis techniques used in this study were Outer Model Test, Inner Model Test, and Moderated Regression Analysis (MRA) Interaction Test using Smart PLS 4.0 analysis tools. The results showed that spiritual intelligence had a positive and significant effect on personal financial management. Intellectual intelligence had a positive and significant effect on personal financial management. Peer group did not significantly moderate the relationship between spiritual intelligence and intellectual intelligence on personal financial management, indicating that peer influence neither strengthens nor weakens the relationship between these two variables and personal financial management.